Phylogeographical patterns of neobalanocarpus heimii (Dipterocarpaceae) for the evolutionary history and chain of custody certification / Tnah Lee Hong - Tnah, Lee Hong (2010)
Tectonic movement and climatic oscillations during the Cenozoic have had dramatic effect on the biota of the tropical rain forest. This study aims to reveal the phylogeography and evolutionary history of a Peninsular Malaysian endemic tropical timber, Neobalanocarpus heimii (Dipterocarpaceae), based on chloroplast DNA (cpDNA) variation. Fifteen haplotypes were identified from 10 intraspecific variable sites of five non-coding cpDNA regions: trnL intron, trnS-trnG spacer, trnG intron, trnK intron and psbK-trnS spacer. Two major genealogical cpDNA lineages of N. heimii were elucidated: a widespread southern and a northern region. The species is predicted to survive in multiple refugia during climatic oscillation: the northwestern region (R1: Sungkop), the northeastern region (R2: Gunung Basur), and the southern region (R3: Panti compartment 16). Recolonization of refugia R1 and R2 could have first expanded into the northern region and migrated both northeastwardly and northwestwardly. Meanwhile, recolonization of N. heimii throughout the southern region could have commenced from refugia R3, and migrated toward northeast and northwest respectively. The populations of Tersang, Pasir Raja and Rotan Tunggal exhibited remarkably high haplotype diversity, which could have been the contact zones that received an admixture of organisms from the northerly and also southerly regions. As a whole, understanding the past history of the extant populations is of the utmost importance when developing sound conservation policies or sustainable management strategies. The inbuilt unique properties of DNA within the timber could serve as tracking and monitoring tools to verify the legality of a suspected timber in the context of illegal logging, forest certification and chain of custody certification. By using N. heimii as an example, a population identification database and a haplotype distribution map in Peninsular Malaysia were generated for authenticity testing based on four cpDNA markers (trnL intron, trnG intron, trnK intron and psbK-trnS spacer). Twenty-one haplotypes were identified from 10 significant intraspecific variable sites. The results clearly revealed that only the northern and southern regions of Peninsular Malaysia were distinguishable. Thus, this database could only be used to determine the wood lot of unknown origin at the regional level. Statistical procedure based on the composition of the wood lot was used to test whether a suspected timber conforms to a given regional origin. Overall, the observed types I and II errors of the database showed good concordance with the predicted 5% threshold, which might indicate that the database is useful to reveal provenance and establish conformity of wood lot from the northern and southern regions of Peninsular Malaysia. In terms of application, this database could be applied to traceability in two different circumstances: (1) to verify the provenance of a wood lot in the context of forest certification and chain of custody certification and (2) to identify the potential population of origin of the suspected illegal harvested wood lot. Wood can be a good source of DNA for various applications in forensic forestry and timber trade if high quality DNA can be retrieved from the dry wood. In order to provide a general guideline for DNA authenticity testing established for N. heimii, this study was designed to evaluate the potential for extracting DNA from the dry wood of N. heimii using the Qiagen kit, CTAB, and CTAB with PTB protocols. Overall, the efficacy of DNA extraction was higher for the cambium and sapwood than for the heartwood tissues. In terms of tissue types, the Qiagen kit yielded higher PCR amplification rates from the cambium tissue, while the CTAB with PTB protocol showed higher amplification rates in the sapwood and heartwood tissues. In order to safeguard the intactness of the DNA, it is recommended that DNA extraction from the wood should be carried out within six weeks after felling for logs and six months after felling for stumps. The results also showed that the amplicon size might not account for the PCR amplification success rate and chloroplast genome yielded higher amplification success rate compared with nuclear genome. Additionally, the PCR amplifications also showed that both the nuclear and chloroplast regions can be retrieved from lumber that was heat-treated at 40 °C to 100 °C, although the phenomena of allelic dropout and inconsistency of genotyping were noted for some of the nuclear regions. In short, the guideline obtained from this study are ready to be used together with the population and individual identification databases developed for the timber tracking system of N. heimii in Peninsular Malaysia.